Patterns of genetic structure and evidence of Egyptian Citrus rootstock based on informative SSR, LTR-IRAP and LTR-REMAP molecular markers - Mohamed Abd S. El zayat; Ahmed H. Hassan; Elsayed Nishawy; Mohammed Ali; Mohamed Hamdy Amar (Journal of Genetic Engineering and Biotechnology, 2021)
Abstract Background Releasing the draft genome of sweet orange provides useful information on genetic structure and molecular marker association with heritable breeding traits in citrus species and their structures. Last decades, microsatellite and retrotransposons are well known as a significant diverse component of the structural evolution. They represented the most potent elements for assessing sustainable utilization of the complicated classification in citrus breeding. Our study was performed to verify the structure analysis and the parentage genetic diversity among the Egyptian citrus rootstocks and the related species. Results Here, the performance of 26 SSR and 14 LTR-IRAP in addition to 20 LTR-REMAP markers have been used to conduct the discriminating power and the status of the genetic structure analysis among twenty specimens of citrus genotypes. As a result, the three markers approach exhibited a remarkable variation among the tested genotypes. Overall, the three markers have different discrimination power; the co-dominant SSR markers can differentiate within the group level only in addition to the species level of sour orange, while the dominant markers LTR-IRAP had the ability to discriminate among the group level in addition to species level and the origin of acids. Similarly, LTR-REMAP is suitable for classifying the group level and species level for mandarins as well the origin of Egyptian acids; probably due to it is integration of SSR and LTR-IRAP techniques. Structure and PCoA results of LTR-REMAP marker in strong support for the group structure of citrus species have been divided into four sets: acids, grapefruit/pummelo, mandarin/orange, and sour orange. Conclusion Our findings of the genetic structure analysis support the monophyletic nature of the citrus species; are able to provide unambiguous identification and disposition of true species and related hybrids like lemon, lime, citron, sour orange, grapefruit, mandarin, sweet orange, pummelo, and fortunella; and resulted in their placement in individual or overlap groups. The outcomes of these results will offer helpful and potential information for breeding programs and conservation approaches as a key stage toward identifying the interspecific admixture and the inferred structure origins of Egyptian citrus rootstock and acid cultivars.